RANCANGAN MEDIA PEMBELAJARAN INTERAKTIF PENDAPATAN NASIONAL DI STMIK STIKOM INDONESIA - Ni Putu Eka Kherismawati (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2019)
In the learning process on the lecture bench, students will naturally choose a way to deliver material that is relaxed, fun, interactive and displays many interesting images. Therefore, we need an interactive learning media. Learning media is a tool that can be used to convey information.In Higher Education, instructional media are used by lecturers as a means to deliver material to students. Often lecturers use teaching materials with visual appearance that are less modern or tend to be monotonous, and are less adapted to student psychology so that what happens students become bored quickly when receiving teaching in class. Today's students who like pictures more than long texts require lecturers to present material that suits their needs so that the teaching and learning process runs effectively and conducively. Students at STMIK STIKOM Indonesia so far in economics only use the media to use power points in the learning process. This causes students to become bored and less interested in the material presented, especially in the National Income material, because this material is divided into six sub-chapters that are descriptive and exact. The lack of student interest in this material can be seen from the lack of student participation in the lecture process.